Bridging Science and Halal Compliance: DNA Analysis Kits Concept for Effective and Educational Authentication - Nurdalila A’wani Abdul Aziz; Faqihah Imtiaz Mohamad Fadzil; Hannah Safiya Mohd Muharir; Mohd Zuhaifah Mohamed Jamil; Dzulfadli Rosli; Wan Kamilah Wan Ibrahim; Ts. Dr. Hatika Kaco (Kolej PERMATA Insan, 2025)
5th Insan Junior Researchers International Conference 2024 (iJURECON 2024) : "STREAM for a better future”/ editors : Ahmad Fuad Mohamad Amin, Ahmad Bazli Ahmad Hilmi, Nurhidaya Mohamad Jan, Norazlina Subani 25-26 October 2024 Organized by : Kolej Permata Insan